Business Model Canvas : Fly away portable fly repellent / Norfarhana Balqis Husin - Husin, Norfarhana Balqis (2020)
According to Business Model Canvas Explained | Enterprising Oxford, n.d. The Business Model Canvas is a business tool used to visualise all the building blocks when you want to start a business. Business Model Canvas is used to validate the market significance of products and services which will be of technology nature in this case. Technology projects are often solutions or processes that solve a technology problem. However the market implementation of such solutions also require that the problem solution is designed to overcome not just technical barrier but also market and business related barriers of costs, customer reach and collaborations and those that pertain to the practical nature of limited initial capacities within the team